1992
DOI: 10.1515/bchm3.1992.373.2.381
|View full text |Cite
|
Sign up to set email alerts
|

A New Family of Proteinases is Defined by Several Snake Venom Metalloproteinases

Abstract: Recently, the complete amino acid sequences have been determined for several snake venom metalloproteinases from the genera Crotalus, Trimeresurus and Lachesis of the Crotalidae family. Among these are both hemorrhagic and nonhemorrhagic metalloproteinases. Despite differences in their molecular weights and activities, they all appear to be related through a single ancestral gene, as observed by the comparison of their amino acid sequences. None of these proteins bear significant similarity to any other known … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
4

Year Published

1992
1992
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 15 publications
0
15
0
4
Order By: Relevance
“…the presence of a fifth tyrosine zinc ligand correlates with the absence of a 'cysteine switch region' [28,29] in the proparts of the corresponding metalloproteinases, presumably reflecting unwanted interference of this tyrosine residue with the mercapto-group of a cysteine peptide.…”
Section: Resultsmentioning
confidence: 99%
“…the presence of a fifth tyrosine zinc ligand correlates with the absence of a 'cysteine switch region' [28,29] in the proparts of the corresponding metalloproteinases, presumably reflecting unwanted interference of this tyrosine residue with the mercapto-group of a cysteine peptide.…”
Section: Resultsmentioning
confidence: 99%
“…The primary structures indicated that the venom enzymes belong to a distinct metalloproteinase Family, all of which contain the HEXXH motif, but which have no significant sequence similarity with any other known metalloproteinases except for this region [9]. However, as can be seen from Fig.…”
Section: Familiesmentioning
confidence: 95%
“…Although this motif is well conserved in these en~mes, the third zinc ligand (the remote glutamic acid) is present only in a few clo;,ely related bacterial metalloendopeptidases [6]. However, high homologies in the sequences following the HEXXH motif have been noticed in several groups of metalloproteases, including collagenases, astacin family proteins, and snake venom metalloprotclnases [7][8][9]. The information on the crystal structure of astacin has greatly facilitated identification of additional zinc ligands in thez~ enzymes [4].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, an analysis of the depth or the distance between the S' 1 -pocket and the catalytic site cavity revealed no significant differences or correlation to hemorrhagic activities for the C. s. scutulatus metalloproteinase models. While the atrolysins have been characterized as hemorrhagic toxins that cleave similar substrates in vitro [55,56], the fact that their catalytic clefts superimpose well with each other but poorly to weakly hemorrhagic C. s. scutulatus metalloproteinases is consistent with this observation.…”
Section: Discussionmentioning
confidence: 70%